Reestruturação urbana e centralidades: análise da região geográfica imediata de Ituiutaba (MG) - Dutra Júnior, Nelio Paulo Sartini (2023)
This study aims to analyze the process of urban restructuring in the Immediate Geographic Region (IGR) of Ituiutaba (MG) and its respective consequences for contemporary centralities, considering, for this, the analysis of urban economic activities in the periods from 1970 to 2020. The selected area for study consists of the municipalities of Ituiutaba (MG), Cachoeira Dourada (MG), Capinópolis (MG), Gurinhatã (MG), Ipiaçu (MG) and Santa Vitória (MG). The analytical perspective of socio-spatial formation was considered, focusing on the economic dynamics that materialize in geographic space. To fulfill the proposed objective, the data analysis included bibliographical research, investigation of quantitative variables and discussion of data from primary and secondary sources. The investigations in the IGR of Ituiutaba (MG) had both intraurban and interurban processes as a scale of approach. With the data discussed, it was possible to elaborate a synthesis atlas with a set of thematic maps about the area under study.